Pathogenesis of atherosclerosis in rheumatoid arthritis - Joko Rilo Pambudi; Harry Isbagio (Indonesian Rheumatology Association, 2014)
Increased morbidity and mortality in patients with rheumatoid arthritis (RA) is largely associated with cardiovascular disease. In this case, the factors that play a role is chronic inflammation. A chronic inflammatory associated with condition which accelerate atherosclerosis and increased cardiovascular morbidity and mortality. Inflammatory and atherogenic mediators have a role in pathogenesis of RA and atherosclerosis. Atherogenesis in RA start when cytokines from the inflamed synovial tissue are released into the systemic circulation. Circulating cytokines affects the function of other tissues such as adipose tissue, skeletal muscle, liver and vascular endothelium that would lead to proatherogenic transformation process such as insulin resistance, prothrombotic effects, pro-oxidative stress and endothelial dysfunction. Size, weight and durationof systemic inflammatory response in RA are the most important factor causing damage. IMT (Intima Media Thickness) measurement on common carotid arteries byB-mode ultrasound is a rapid non-invasive examination of the structural anatomy, reproducible and relatively low risks that are advantageous for assessing therisk of cardiovascular disease and monitoring disease progression.